Toward an Entropy-based Method for Multi-Physics Optimization of Additively Manufactured Cellular Materials - Tyler D. Smith; Dhruv Bhate (Additive Manufacturing Letters)
This study investigates a novel approach using thermodynamic first principles for optimizing the design of a cellular material for requirements-driven multi-physics, multi-objective optimization. To accomplish this, a generalizable multi-objective optimization method was developed to minimize total exergy destruction as a result of any number of irreversibilities quantified at the level of the unit-cell topology. The method was demonstrated by optimizing the topology of a regular honeycomb to minimize irreversibilities due to thermal losses, fluid friction, mechanical strength, and mass. Using this approach, the method was able to quantitatively optimize the design to minimize thermodynamic irreversibilities and qualitatively understand the interaction between multiple, or individual objective functions to optimize systems for specific use cases. Furthermore, the Relative Exergy Destruction number was proposed as a systematic method for assessing design trade-offs by evaluating the relative contribution of each irreversibility quantified in the optimization.